Involvement of phosphatidylserine receptors in the skeletal muscle regeneration: therapeutic implications. Issue 4 (5th June 2022) - Szondy, Zsuzsa; Al‐Zaeed, Nour; Tarban, Nastaran; Fige, Éva; Garabuczi, Éva; Sarang, Zsolt
Abstract: Sarcopenia is a progressive loss of muscle mass and strength with a risk of adverse outcomes such as disability, poor quality of life, and death. Increasing evidence indicates that diminished ability of the muscle to activate satellite cell‐dependent regeneration is one of the factors that might contribute to its development. Skeletal muscle regeneration following myogenic cell death results from the proliferation and differentiation of myogenic stem cells, called satellite cells, located beneath the basal lamina of the muscle fibres. Satellite cell differentiation is not a satellite cell‐autonomous process but depends on signals provided by the surrounding cells. Infiltrating macrophages play a key role in the process partly by clearing the necrotic cell debris, partly by producing cytokines and growth factors that guide myogenesis. At the beginning of the muscle regeneration process, macrophages are pro‐inflammatory, and the cytokines produced by them trigger the proliferation and differentiation of satellite cells. Following the uptake of dead cells, however, a transcriptionally regulated phenotypic change (macrophage polarization) is induced in them resulting in their transformation into healing macrophages that guide resolution of inflammation, completion of myoblast differentiation, myoblast fusion and growth, and return to homeostasis. Impaired efferocytosis results in delayed cell death clearance, delayed macrophage polarization, prolonged inflammation, and impaired muscle regeneration. Thus, proper efferocytosis by macrophages is a determining factor during muscle repair. Here we review that both efferocytosis and myogenesis are dependent on the cell surface phosphatidylserine (PS), and surprisingly, these two processes share a number of common PS receptors and signalling pathways. Based on these findings, we propose that stimulating the function of PS receptors for facilitating muscle repair following injury could be a successful approach, as it would enhance efferocytosis and myogenesis simultaneously. Because increasing evidence indicates a pathophysiological role of impaired efferocytosis in the development of chronic inflammatory conditions, as well as in impaired muscle regeneration both contributing to the development of sarcopenia, improving efferocytosis should be considered also in its management. Again applying or combining those treatments that target PS receptors would be expected to be the most effective, because they would also promote myogenesis. A potential PS receptor‐triggering candidate molecule is milk fat globule‐EGF‐factor 8 (MFG‐E8), which not only stimulates PS‐dependent efferocytosis and myoblast fusion but also promotes extracellular signal‐regulated kinase (ERK) and Akt activation‐mediated cell proliferation and cell cycle progression in myoblasts.